Asian graduate students as skilled labor force serving Empire: a postcolonial analysis of the model minority stereotype shaped and ingrained through transnational experiences - Kim, Eun Hee (Kansas State University, 2018)
It has been 50 years since the notion of the model minority was first used to describe Asian Americans in the United States (Petersen, 1966). In the past decade, there has been substantial scholarly growth in the model minority research, and researchers have identified racism hidden behind the notion. However, previous research has mainly addressed the model minority stereotype in the regional context with similar research topics that produce similar findings, which requires a new research paradigm to be established. To meet this theoretical and contextual need, this study locates the model minority discourse in postcolonialism, especially in the context of Empire as global sovereign power with no concrete form, viewing the model minority stereotype as Empire’s controlling strategy that ethnicizes all Asians on the globe into its “global capitalist hierarchy” (Hardt & Negri, 2000). Empirically, this study examines how the model minority stereotype is shaped, developed, and ingrained in the transnational experience of Asian international graduate students who pursue careers in the United States after their degree completion as a bridge to their future. Findings from participants’ narratives show that they became aware of their Asianness through their transnational experience and gradually embraced the hardworking image of Asians through repeated environmental and interactional input of the image. Participants also expected higher economic and social status in their home countries as a result of their degrees and work experience obtained in the United States, with Orientalist values people in their home countries attach to their U.S.-earned credentials. Asian intellectuals educated in the West, represented by the United States, serve Empire’s capitalist maintenance and expansion as a transnational workforce while seeking their self-interest and transnational competitiveness. This raises an interdisciplinary and intersectional need to empower higher education to be critically aware of the current context of Empire and globalization.
Keywords: Model minority stereotype; Empire; Globalization; Postcolonialism; Asians; Asian Americans